The influence of gratitude on pre-service teachers’ career goal self-efficacy: Chained intermediary analysis of meaning in life and career calling - Zhang, Sensen; Tang, Yulun; Yong, Shaohong (Frontiers in Psychology, 2022)
Objective The aim of the study was to explore the relationship among gratitude, meaning in life (MIL), career calling, and career goal self-efficacy (CGSE) of the pre-service teachers in the Free Teacher Education program in China and the internal mechanism of action. Methods In this study, gratitude, MIL, career calling, and CGSE questionnaires were used to investigate 801 pre-service teachers. IBM SPSS 25.0 and AMOS 24.0 were used for data processing, and SPSS macro program Model 6 was used for the mediating mechanism. Results (1) Gratitude was positively correlated with MIL and career calling. MIL was positively correlated with career calling. Gratitude, MIL, and career calling were significantly and positively associated with CGSE. (2) Gratitude influences pre-service teachers’ CGSE mainly through the independent intermediary of MIL and career calling, and the chain intermediary of MIL→career calling, three indirect effects. Conclusion Gratitude indirectly predicts CGSE of pre-service teachers not only through the independent intermediary of MIL and career calling but also through the chain intermediary of MIL and career calling.